Deep green resistance : strategy to save the planet - McBay, Aric (Seven Stories Press, 2011)
In their long-awaited how-to guide for the deep green ecology movement, Aric McBay, Lierre Keith, and Derrick Jensen make the case that technology won't fix the environmental problems we face, and consumption, no matter how green, is only accelerating the earth's decline. But there is a way to save the planet, the authors contend, if we are brave enough to accept it: we must join together and dismantle the industrial economy. Rich with historical examples of successful resistance movements, a clear-sighted analysis of the pitfalls of pop environmentalism, and a comprehensive presentation of strategic options from nonviolence to guerrilla warfare, Deep Green Resistance is a plan of action for anyone ready to stop waiting for change and start fighting for it. --Book Jacket.